Improving The Dimensions of The Citizenship Profile of Graduates, through National Songs in Arts and Culture Learning: A Classroom Action Research Study in Senior High Schools - Prihantoro, Puthut; Fauziati, Endang; Haryanto, Sigit (Proceedings International Conference on Education Innovation and Social Science, 2025)
The low awareness of students towards civic values, such as nationalism, love of the country, and social concern, is a worrying phenomenon in today's education world, especially at the secondary education level. The lack of student involvement in national-themed activities and the lack of understanding of national songs indicate the need for learning strategies that can instill these values effectively. This study aims to improve the dimensions of the civic graduate profile through the use of national songs in arts and culture learning. The method used is the Classroom Action Research (CAR) model of Kemmis & McTaggart, which is carried out in two cycles with stages of planning, action, observation, and reflection. The subjects of the study were grade XI students at a high school. Data collection techniques include observation, Likert scale questionnaires, interviews, and documentation. The results of the study showed that there was a significant increase in the civic aspect of students after the implementation of national songbased learning. The average score of the civic questionnaire increased from 3.12 in the preaction to 4.21 in the post-action. In addition, observations show an increase in students' active involvement in learning, as well as the growth of reflective awareness of the meaning of national songs. This study proves that national songs are not only an expression of art, but also an effective educational medium in instilling national character values. The benefits of this study are to provide an alternative learning approach that is contextual, meaningful, and able to support the strengthening of the Pancasila Student Profile, especially in the citizenship dimension.